Finance and Economic Development : Policy Choices for Developing Countries - Demirgüç-Kunt, Aslı (World Bank, Washington, DC, 2012)
The empirical literature on finance and development suggests that countries with better developed financial systems experience faster economic growth. Financial development-as captured by size, depth, efficiency, and reach of financial systems-varies sharply around the world, with large differences among countries at similar levels of income. This paper argues that governments play an important role in building effective financial systems and discusses different policy options to make finance work for development.